Low satisfaction with normative life domains in adolescents with anorexia nervosa. (2nd March 2021) - van Doornik, Sanne F. W.; Ostafin, Brian D.; Jonker, Nienke C.; Glashouwer, Klaske A.; de Jong, Peter J.
Abstract: Objective: Low satisfaction with normative life domains might be an important factor in the persistence of anorexia nervosa (AN). Initial evidence in non‐clinical samples showed that lower satisfaction with normative life domains was related to more intense eating disorder symptoms. As a critical next step, the current study examined satisfaction with normative life domains in a clinical sample. Specifically, the present study tested whether adolescents with AN reported lower satisfaction with normative life domains than adolescents without an eating disorder. Method: Adolescents with AN ( n  = 69) and adolescents without an eating disorder matched on age, gender and educational level ( n  = 69) completed the Brief Multidimensional Students' Life Satisfaction Scale to assess satisfaction with five life domains (family, friendships, school, self and living location) and life in general. Results: Adolescents with AN reported significantly lower satisfaction with normative life domains than the comparison group. Subsequent analyses showed that this overall group difference was primarily driven by adolescents with AN reporting lower satisfaction with the self, school experience and life in general. Conclusions: Findings supported the hypothesis that adolescents with AN show relatively low satisfaction with meaningful, non‐AN‐related life domains. This points to the potential relevance of enhancing satisfaction with specific life domains to optimize treatment effectiveness.